Pharmacokinetic research in children: an analysis of registered records of clinical trials. Issue 1 (9th August 2011) - Viergever, Roderik F; Rademaker, Carin M A; Ghersi, Davina
Abstract : Background: Reported off-label/unlicensed prescribing rates in children range from 11% to 80%. Research into pharmacokinetic profiles of children's medicines is essential in the creation of more knowledge on the safety and efficacy of medicines in children. This study investigated how often pharmacokinetic data are collected in clinical trials of medicines in children by analysing registered records of clinical trials. Methods: The registered records of all clinical trials in children that were recruiting on 22 May 2009 were identified on the International Clinical Trials Registry Platform using a Clinical Trials in Children search filter. The records of trials in children below 12 years of age, in which the intervention was one or more medicines, were assessed for evidence that pharmacokinetic data would be collected. Results: Of 1081 eligible trial records, 257 (24%) declared that pharmacokinetic data would be collected. Of these trials, 199 (77%) recruited in Northern America; recruitment in all other regions was below 20%. Trials recruited most often in children over 2 years of age (74%), and least often in newborn infants (32%). Most trials researched medicines in the field of cancer (29%). Trials investigated one-third of the medicines that were indicated as a priority for pharmacokinetic research by the European Medicines Agency. Conclusions: There is a need for increased knowledge of the pharmacokinetic profiles of children's medicines. The amount of currently ongoing pharmacokinetic research does not seem to address adequately the lack of knowledge in this area. This study sets a baseline for monitoring of future progress on the amount of ongoing pharmacokinetic research in children.